Działalność wydawnicza i prasotwórcza lwowskiej Izby Handlowej i Przemysłowej (do 1918 roku) - Meus, Konrad (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2021)
Among the most important economic institutions operating in Lviv in the times of Galician autonomy were the Chamber of Commerce and Industry and its subordinate Institute of Technology, which had existed since 1909. The most important functions of the Institute included publishing activities on the book and press markets. The Institute of Technology specialised in publishing trade titles targeted at Galician industrial entrepreneurs and craftsmen. Particularly noteworthy was a biweekly magazine called “Rękodzielnik” published between 1912 and 1914. Before the outbreak of World War I, it was the most widely read magazine in Lviv and Eastern Galicia dedicated to small and medium-sized craft businesses. It published primarily specialised articles on the latest production techniques used in crafts and industry, as well as journalistic texts that attempted - mostly successfully - to discuss vital issues related to the current economic policy of the state (Austria-Hungary) and the country (Galicia). In addition, the Institute of Technology (and, through it, the Chamber of Commerce and Industry) also made its presence known in the book market. Only in the years preceding the war were several highly specialised books on handicraft production methods and science materials published under the Institute’s name. The Institute’s publishing activity came to a halt temporarily during the Great War and the ensuing Russian occupation of Lviv. The residents of Lviv had to wait until the early 1920s for the Chamber and Institute of Technology to resume their publishing activities